Se réconcilier « entre victimes » pour tenir la lutte : la coordination transversale des familles de disparus au Liban et de leurs alliés de la justice transitionnelle - Yves Mirman (L’Année du Maghreb)
The issues of reconciliation in Lebanon are linked to civil war legacies, one concerns families of the missing persons from the conflict (1975-1989). Supported by human rights and transitional justice organizations, they have been asserting their struggle for 40 years in a dispersed but also united manner. Based on sociology of collective action and without prescriptive approach of the post-conflict, this article describes transversal logics of coordination between militant groups, beyond the role of the leaders. What they reveal about the stakes of reconciliation in Lebanese society? Accused of being “threats to civil peace” by the authorities and former warlords, these activists - often women - have been trying to assert their cause over time, from the 1980s to 2018. Using reports from human rights organizations, activist archives and interviews, I describe three coordination processes: the comparison of the cases of the disappeared, which allows them to share the same uncertainties; the conflicting operations of labeling both the cause and the common objects of their struggle; and the showing of their reunification beyond the logics of confessionalism. The analysis of these transversal processes of coordination of collective action, over the long time of the struggle, allows us to define several issues of the post-conflict in Lebanon.